مسند زيد بن علي بين الرواية والتركيب: دراسة إسنادية تحليلية: (Musnad Zaid bin Ali between Narration and Composition: Analytical Reference Study) - al-Marri, Saeed mohd (Online Journal of Research in Islamic Studies, 2023)
The aim of this research is to verify the attribution of Zayd’s book to him by looking at two important factors: Checking the attribution of the book from us to the author, and the book’s popularity in the scientific community. Looking at the chain of transmission, a uniqueness was found, which continued in twelve layers after Zaid. It is a severe uniqueness that is not common to happen to famous books, with its inclusion of some liars. When the book’s popularity and its distribution in the scientific community were examined, it was found that from the third to the sixth century AH neither Zaid’s close relatives nor the most well-known Zaidi imams who attempted to emulate his doctrine were aware of its existence, until Judge Jaafar Bin Ahmad Bin Abdul Salam Al-Bahlouli announced its unique existence and its chain of transmission. The study concluded that the book was fabricated for Zaid, that his creator is the Judge Al-Bahlouli, who is unique in its chain of transmission. He is the one for whom the book is famous, and that some chain of narrators was then composed to it. The research also revealed that what the terminologists mention about leniency in chains of transmission to authors does not apply to Zaid’s chain of transmission because it violates a number of conditions they recognize in this regard.